PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 013 TELUK PIYAI KECAMATAN KUBU - Supriyati '; Zariul Antosa; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The background of the research is the process of learning and teachingfourth grade SDN 013 subdistricts Piyai Gulf Kubu Rokan Hilir in sciencesubjects which are still dominated by the teacher so that students become passive,as well as materials provided by the teacher and the learning outcomes are notsatisfactory with the value - average KKM is below 68 this study aims todetermine the learning outcomes after direct learning both individually andclassical to class IV student learning outcomes in science subjects SDN 013 GulfPiyai Kubu district of Rokan Hilir. This study was conducted on 20 studentsconsisting of 8 men - men and 12 women. Data were collected throughobservation using the observation sheet for learning data directly and throughdaily tests for data belajar.Hasil research results indicating that directinstructional model individually significantly affect student learning outcomes.Where students who otherwise completed their study of 20 students. Viewedclassically turns direct instructional model also significantly affect the gainmastery by 30% by value - average 74.5. This means that the direct instructionalmodel can improve student learning outcomes, both individually and classical.Keywords : Direct Learning, science Learning Outcomes